Autologous Transplantation for the Treatment of Leukemia - Visacre, Paulo Henrique Marquiori (2011)
Hematopoietic stem cells transplant (HSCT) has been used in the treatment of hematologic diseases for more than thirty years. Progress in immunology, such as identification immune process mediators, and advances in infectiology, such as new diagnostic methods and new antibiotics, have contributed towards the expansion of indications and the increase in the procedure’s success rate. There are three transplantation’s types: allogenic, autologous and the singenic. The bone marrow in allogenic transplant is taken from a previously selected donor to test blood compatibility. Whereas the singenic transplant occurs between identical twins, in the autologous transplant, the progenitor cells are the patient’s. The autologous transplantation is an important therapy for the treatment of leukemia in cases where the would-be transplant patient does not have a compatible donor. This type of transplantation was enhanced during the 1970s as an alternative to allogenic transplant because of difficulties in finding compatible donors. Leukemia is a disease in which frequently the patients need a transplant so that they may survive free from the disease. Thus, the autologous transplantation is an important therapy for the treatment of leukemia as it is a procedure where the donor is the very patient who will undergo the transplant. This type of therapy in the treatment of leukemia is important because its applicability and its positive results in the patients’ survival have increased.